2003
DOI: 10.1128/iai.71.10.5549-5555.2003
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of, and Immunologic Memory to, a Reduced Primary Schedule of Meningococcal C-Tetanus Toxoid Conjugate Vaccine in Infants in the United Kingdom

Abstract: It has been previously shown that one of the three meningococcal C conjugate (MCC) vaccines introduced in the United Kingdom proved highly immunogenic after the first dose of a three-dose schedule, with evidence of immune memory after dose 3. Thus, in infants a one-or two-dose schedule of this MCC vaccine, conjugated to tetanus toxoid (TT), may suffice. Healthy infants (n ‫؍‬ 586) were randomized to receive either one (group 1), two (group 2), or three (group 3) doses of MCC-TT vaccine with a 10-g polysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 21 publications
5
63
0
4
Order By: Relevance
“…Following boosting, a lower SBA GMT was observed in the 2 dose priming group, with a GMT of 1538.0 (95%CI 1381.1-1712.6) compared to GMTs of 2472.1 (95%CI 2226.3-2745.0) and 1874.8 (95%CI 1684.4-2086.6) in the 4 month and 6 month groups. Lower SBA GMTs in the 2 dose priming group is consistent with data reported by Richmond et al, 5 and Borrow et al, 16 showing the quantity of antigen administered during priming correlates positively with post-primary SBA levels but negatively with the magnitude of the booster response. The reduced response in the 2 dose group may also be attributed to protein carrier-induced epitope suppression, with a dose dependent suppression of the antigen response.…”
Section: Evidence Supporting a Single Infant Priming Dosesupporting
confidence: 81%
“…Following boosting, a lower SBA GMT was observed in the 2 dose priming group, with a GMT of 1538.0 (95%CI 1381.1-1712.6) compared to GMTs of 2472.1 (95%CI 2226.3-2745.0) and 1874.8 (95%CI 1684.4-2086.6) in the 4 month and 6 month groups. Lower SBA GMTs in the 2 dose priming group is consistent with data reported by Richmond et al, 5 and Borrow et al, 16 showing the quantity of antigen administered during priming correlates positively with post-primary SBA levels but negatively with the magnitude of the booster response. The reduced response in the 2 dose group may also be attributed to protein carrier-induced epitope suppression, with a dose dependent suppression of the antigen response.…”
Section: Evidence Supporting a Single Infant Priming Dosesupporting
confidence: 81%
“…NeisVac-C has also been reported to induce putative levels of protection in 92% of infants, with a GMT of 491 (95% CI, 275 to 877), when given at 2 months of age with a DTaP 3 /Hib-TT vaccine (Infanrix-Hib; GSK) though without concomitant PCV7 (26). A number of studies have reported good immunogenicity of a single dose of NeisVac-C when given in infancy with wP-containing vaccines (5,22).…”
Section: Discussionmentioning
confidence: 99%
“…23,27 The improved post-booster immunogenicity of fewer priming doses is well described for meningococcal C conjugate vaccines and is believed to be due to lower total antigen exposure favoring differentiation of B lymphoblasts into memory B cells instead of antibody-generating plasma cells. 14,15 In pneumococcal conjugate vaccines, a study of Fijian infants receiving 1 PCV7 priming dose followed by the 23-valent pneumococcal polysaccharide vaccine at 12 months had higher IgG GMCs for serotypes 4, 9V, and 19F compared with those who had been primed with 2 or 3 PCV7 doses. 13 Similarly, infants receiving a lower antigen-containing investigational tetravalent pneumococcal conjugate vaccine for priming had higher booster responses than those who had received the higher antigencontaining preparation.…”
Section: Figurementioning
confidence: 99%